In vitro blood flow in circular PDMS microchannels: effect of the flow rate and hematocrit - Garcia, Valdemar (2010)
Recently, Lima et al. (1) has performed confocal micro-PIV measurements on the blood flow through straight PDMS microchannel. In the study they have observed that the formation of the cell free layer is enhanced as the cross section ratio increases. However, the cross section ratio is not the only parameter that contributes for the creation of the cell-free layer. Hence, several other physical and hemorheological factors (such as flow rate, hematocrit, viscosity and cell deformability) need to be investigated in order to make use on the physics of microfluidics to either develop new lab-on-chip devices or to optimize the design of the existent microfluidic chips. The main aim of the present study is to show the effect of both flow rate and hematocrit on the blood flow and cell behavior. The circular polydimethylsiloxane (PDMS) microchannels were fabricated by using wire casting technique and the experiments were carried out by using dextran 40 containing different fractions of red blood cells (RBCs). The in vitro blood flow was measured by means of video microscopy and image analysis. Additionally, the pressure drop was also measured.